Woman as A Dirty Machine: A Question of Objectification on E.E. Cummings - Pratiwi, Titis (UI Scholars Hub, 2015)
The pervasiveness of female objectification in the treatment of women by men has been called out as a manifestation of gender hierarchy and domination. This research analyzed the figurative languages used in E.E. Cummings’ poem first she like a piece of ill-oiled to identify his treatment of women seen through the illustration of the persona’s actions, thoughts and feelings. Dynamics of the personas’ sexual relationships are then identified to analyze how aspects of objectification appear in the relation between men and women. In order to reinforce the notion of objectification, dehumanization as its extension is utilized as a supporting theory. It is found that practices of female objectification occur in the poem with varying degrees of intensity and ways that it is conducted. However, the objectification is concealed by the poem’s presentation of women as a sexually liberated being, yet in practice, her sexuality is still being objectified. The objectification extends up to the conduct of dehumanization which reduces the women into a dirty mechanical object.